(untitled) (Research, Society and Development, 2021)
Objective: To analyze the development of competencies of physical therapist professors in a public institution in the state of Goiás, Brazil, and whether their academic performance strategies have interdisciplinary and public health oriented approaches. Method: A cross-sectional study with a quantitative and qualitative approach was carried out using a mixed questionnaire for professors, with open, closed and multiple choice questions. The sample was composed of 24 professors from the State University of Goiás, Brazil. Results and discussion: Teaching practice in higher education in Brazil, in general, tends to begin without previous preparation and intuitively. The interviewees point to physical therapy as an area of growth, but there is a lack of financial recognition. It is understood that physical therapy is an essential profession in the three levels of health care, although it is still associated only with the tertiary level. The academic training interferes incisively in the way these professionals act, in what refers to public health, the knowledge about the system is fundamental. The perspective is of a care and training more linked to the biopsychosocial model and technology. Conclusion: The practical performance of physical therapy is a direct reflection of academic learning and therefore the teachers of the area must and try to seek improvements in the exercise of teaching, since the practices and management have direct repercussions on society, especially on the topic of public health.